Thin-walled structures with structural imperfections : analysis and behavior - Godoy, Luis A. (Luis Augusto) (Pergamon, 1996)
Thin-walled structures are designed with advanced numerical analysis techniques and constructed using sophisticated fabrication processes. There are, however, a number of factors that may result in a structure that is not exactly coincident with what was considered during the design calculations. These features may be associated with changes in the properties of the structure, in the geometry, and many others. But even small changes in the structure may sometimes produce significant changes in the response. The present work is intended to introduce professionals and researchers to the effects.